Optimasi Rute Distribusi Menggunakan Metode Tabu Search Perusahaan Daerah Air Minum (PDAM) Tirta Bangun Kulon Progo - Siti Dinar Rezki Ramadhani; Hafizhta Aryunda Tanggono; Rif’an Yusuf (Proceedings Series on Physical & Formal Sciences, 2021)
Logistics management is known as distribution and transportation management, while others call it physical distribution management. Distribution activities are very important for companies to deliver a product to consumers across various regions. The Regional Drinking Water Company (PDAM) Tirta Binangun Kulon Progo is one of the companies that produce Bottled Drinking Water (AMDK) under the product name AirKu. The high demand for AMDK AirKu products in 240 ml cup packaging was causing limited vehicles and the absence of a clear standard distribution route, which caused the distribution process to be carried out randomly. Therefore, to overcome the company's problems, it is possible to determine the Vehicle Routing Problem (VRP) route with the CVRP approach, where the route determination is based on fleet capacity. The method used was tabu search using the MATLAB application to minimize the bottled product delivery route traveled. The results obtained were the total distance traveled by 284.9 km. The proposed route had a distance savings of 118.26 km, which is better than the company route.